Juveniles incarcerated in U.S. adult jails and prisons, 2002-2021 - Zeng, Zhen (Just the stats, 2023)
This web report presents data on juveniles (persons age 17 or younger) who are held in adult correctional facilities. It shows changes in the number of juveniles held in adult prisons and jails between 2002 and 2021. It also provides data on juveniles by sex and by whether they were held in federal prisons, state prisons, or local jails.